Minimum Wages and Firm Exports: Evidence from Vietnamese Manufacturing Firms - Dong Xuan Nguyen (East Asian Economic Review (EAER), 2021)
This paper investigates the relationship between the minimum wage and firm's export behavior by using firm-level data of Vietnamese manufacturing enterprises over the period 2010 through 2015. In this regard, I apply the logistic regression model for the probability of exporting and the differences-in-differences analysis to the data, and find that raising minimum wage standards drive no new exporters but a rise in a firm's export sales. Less productive and more labor-intensive firms raise their amount of exports in response to increasing minimum wage levels. Being exposed to increasing minimum wage levels makes a firm under-perform in terms of export sales compared to non-exposed firms.
Keywords: F16; F23; J38; O14; 330; Wages; Exports; Vietnam